Reproducible research in pattern recognition : second International Workshop, RRPR 2018, Beijing, China, August 20, 2018, Revised selected papers /: second International Workshop, RRPR 2018, Beijing, China, August 20, 2018, Revised selected papers. (2019) - Unknown
No abstract available